ГІБРИДНІ ФІЛЬТРОКОМПЕНСУЮЧІ ПЕРЕТВОРЮВАЧІ ДЛЯ ТРИФАЗНИХ СИСТЕМ З НЕЛІНІЙНИМИ ТА ЗМІННИМИ НАВАНТАЖЕННЯМИ - Жаркін , А.Ф.; Новський , В.О.; Малахатка , Д.О. (Інститут електродинаміки НАН України, Київ, 2015)
The basic principles of hybrid filter-compensating converters (HFCC) development that are made on base of distribution STATCOM and regulated filter-balancing device (RFBD). HFCC intended to compensate load current in neutral of four-wire network, to provide load voltage control (or voltage stabilization) as well as harmonic current filtering in network are considered. The simulation results of RFBD operating modes for different types and power of loads are presented. References 5, tables 2, figures 4.